(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2022)
In this article readers can be aware of the role of friendship of nations in the world. Basicly, this article is devoted to the importance of value and its importance in our daily life. Today it is the most important issue in upbringing the youth according to the values which came from our ancestors. Because our future depends on present-day youth. So friendship of nations and values have great influence of young generation. Today’s spiritual and education efforts help to bring up the youth as a loyal to the country and spiritual perfected person.